Reducing human effort in web data extraction - Guo, J (2017)
The human effort in large-scale web data extraction significantly affects both the extraction flexibility and the economic cost. Our work aims to reduce the human effort required by web data extraction tasks in three specific scenarios. (I) Data demand is unclear, and the user has to guide the wrapper induction by annotations. To maximally save the human effort in the annotation process, wrappers should be robust, i.e., immune to the webpage’s change, to avoid the wrapper re-generation which requires a re-annotation process. Existing approaches primarily aim at generating accurate wrappers but barely generate robust wrappers. We prove that the XPATH wrapper induction problem is NP-hard, and propose an approximate solution estimating a set of top-k robust wrappers in polynomial time. Our method also meets one additional requirement that the induction process should be noise resistant, i.e., tolerate slightly erroneous examples. (II) Data demand is clear, and the user’s guide should be avoided, i.e.., the wrapper generation should be fully-unsupervised. Existing unsupervised methods purely relying on the repeated patterns of HTML structures/visual information are far from being practical. Partially supervised methods, such as the state-of-the-art system DIADEM, can work well for tasks involving only a small number of domains. However, the human effort in the annotator preparation process becomes a heavier burden when the domain number increases. We propose a new approach, called RED (abbreviation for “redundancy”), an automatic approach exploiting content redundancy between the result page and its corresponding detail pages. RED requires no annotation (thus requires no human effort) and its wrapper accuracy is significantly higher than that of previous unsupervised methods. (III) Data quality is unknown, and the user’s related decisions are blind. Without knowing the error types and the error number of each type in the extracted data, the extraction effort could be wasted on useless websites, and even worse, the human effort could be wasted on unnecessary or wrongly-targeted data cleaning process. Despite the importance of error estimation, no methods have addressed it sufficiently. We focus on two types of common errors in web data, namely duplicates and violations of integrity constraints. We propose a series of error estimation approaches by adapting, extending, and synthesizing some recent innovations in diverse areas such as active learning, classifier calibration, F-measure estimation, and interactive training.